Acquisition of MACPF domain-encoding genes is the main contributor to LPS glycan diversity in gut Bacteroides species. Issue 12 (December 2018) - McEneany, Valentina; Coyne, Michael; Chatzidaki-Livanis, Maria; Comstock, Laurie
Abstract The ability to antagonize competing strains and species is often important for bacterial fitness in microbial communities. The extent to which intra-species antagonism drives phenotypic diversity of bacterial species is rarely examined in a comprehensive manner at both the genetic and phenotypic levels. Here we show that for nine abundant human gutBacteroides species examined, there are only a few LPS glycan genetic types. We show that for a givenBacteroides species, there is a predominant lipopolysaccharide (LPS) glycan locus present in the majority of strains. However, other strains have replacements of glycosyltransferase-encoding genes, in most cases, adjacent to a membrane attack/perforin (MACPF) domain-encoding gene not present in the predominant type. We show that the MACPF genes present in LPS glycan biosynthesis loci of fourBacteroides species encode antimicrobial proteins and inBacteroides vulgatus andBacteroides dorei, we show the MACPF toxin targets the LPS of strains with the predominant LPS glycan locus. By a combination of gene deletion and replacement, we converted a MACPF toxin-producing strain into a sensitive strain. Genetic diversity of LPS glycan biosynthesis regions inBacteroides is similar to phage serotype conversion whereby the receptor is altered to render the strain immune to infection/toxicity, and is a rare example in bacteria of toxin immunity conferred to the toxin-producing strain by replacement of genetic material to modify the receptor rather than by a cognate immunity protein.